Self-Sufficiency Discourse in the Prabowo Era: A Study of the Inaugural and August 15, 2025 Speeches - Mujahiddin, Mujahiddin; Nasution, Nurhasanah; Martinelli, Ida (UMSU, 2025)
This article aims to examine how the discourse of self-sufficiency is in the Prabowo administration era. The narratives analyzed are the texts of President Prabowo's speeches at the Presidential Inauguration, and the text of President Prabowo's State Address on August 15, 2025, which includes the text of the speech on the 80th Anniversary of the Independence of the Republic of Indonesia and the text of the speech on the Introduction/Information on the Bill on the State Budget for the 2026 Fiscal Year. This study uses a descriptive qualitative approach with a critical discourse analysis (CDA) perspective proposed by Norman Fairclough.